Water Quality Evolution of Rio de Janeiro City Beaches - Maria Carolina Chalegre-Touceira; Alexandre Carlos Barreto; Natália da Silva Menezes; David Man Wai Zee (Orbital: The Electronic Journal of Chemistry, 2018)
Rio de Janeiro city is famous worldwide for its beaches. Therefore, it is necessary to analyze the monitoring of water quality data, since the pollution is a risk to the population health. It was made a temporal evolution analysis of the recreational water quality of Rio de Janeiro city main beaches. Thermotolerant Coliforms’ (TtC) data collected by the Instituto Estadual do Ambiente (INEA) from 1995 to 2015 were related with the CONAMA 274/2000 Resolution limits criteria. It was observed that Barra da Tijuca western portion, Leblon, Ipanema, Arpoador, Copacabana, Leme, Vermelha and Urca beaches showed an overall improvement of their water quality conditions over the analyzed period. São Conrado and the eastern corner of Barra da Tijuca beach have shown worsening. Joatinga beach remained stable. Flamengo and Botafogo beaches showed variable conditions over time, but always presenting poor water quality conditions. It was verified that the determining factors for a beach having inappropriate water quality were the existence of canals that dump sewage and urban runoffs. Another relevant factor was the location of beaches within the confined and polluted waters of Guanabara Bay. This study can be used as a useful tool for a more efficient management for urban beaches.DOI: http://dx.doi.org/10.17807/orbital.v10i4.1072